Pembuatan Biodiesel Dari Minyak Sawit Off-Grade Menggunakan CaO/Fly Ash Sebagai Katalis Pada Tahap Transesterifikasi - Viqrie Wahyudi; Zuchra Helwani; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Indonesia needs the development of renewable energy. Biodiesel is one of renewable energy that formed as liquid fuel and has same property with petrodiesel. Biodiesel is able to be synthesis from off-grade palm oil using CaO/fly ash as catalyst in transesterification process. Employing fly ash as support in CaO has a good impact due to environmentally friendly, good economic potential and the utilization of Ca compound in fly ash. Biodiesel production in this study aims is to see the influence of reaction temperature, molar ratio of methanol and oil and concentration of CaO/fly ash towards biodiesel yield. The process was conducted through reaction of esterification and followed by transesterification reaction. Processing the data in this study was conducted by Response Surface Methodology (RSM) using Design Expert 7.0 program which is experimental design determined by Central Composite Design (CCD) which consists of three variables. The highest result of biodiesel yield was 59,34% at 70oC reaction temperature, molar ratio of methanol : oil 6 : 1 and catalyst concentration of CaO/fly ash 6%-w. Biodiesel characteristics like as density, kinematic viscosity, acid value and flash point has been appropriate by Indonesian biodiesel standard. The most significant process condition affecting the yield of biodiesel was catalyst concentration.Keywords: biodiesel, off-grade palm oil, catalyst, fly ash, transesterification